HEAVY METALS IN CULTIVATED SOIL AND PLANTS OF DAMOUR URBAN AREA - LEBANON - Fadel, D.; Argyraki, A.; Papageorgiou, S.; Kelepertzis, E. (Bulletin of the Geological Society of Greece, 2016)
Preliminary data on heavy metals concentrations in soil and edible plants of DamourLebanon are presented for the first time. Concentration ranges of Zn, Cu, Ni, Cr, Co, Mn, Fe, Ba, Pb and Cd in soils and vegetables collected from urban allotments in Damour were determined and assessed taking into account the pseudototal (extracted by aqua regia) and mobilizable (0.43 M acetic acid extractable) concentrations of the elements in the rhizosphere soil of the plants as well as the total concentrations in edible plant tissue. Average elemental concentrations in urban allotments are low in general. No detectable concentrations of the non-essential heavy metals Pb and As were measured in the studied plants while concentrations of micronutrient elements in plants were within normal ranges. The collected data indicate that previous land use is an important factor controlling heavy metal content in soil and that there is a complex mechanism controlling micronutrient uptake by plants.